Innate immunity and genetic determinants of urinary tract infection susceptibility. Issue 1 (February 2015) - Godaly, Gabriela; Ambite, Ines; Svanborg, Catharina
<x xml:space="preserve">Abstract</x> Purpose of review Urinary tract infections (UTIs) are common, dangerous and interesting. Susceptible individuals experience multiple, often clustered episodes, and in a subset of patients, infections progress to acute pyelonephritis (APN), sometimes accompanied by uro-sepsis. Others develop asymptomatic bacteriuria (ABU). Here, we review the molecular basis for these differences, with the intention to distinguish exaggerated host responses that drive disease from attenuated responses that favour protection and to highlight the genetic basis for these extremes, based on knock-out mice and clinical studies. Recent findings The susceptibility to UTI is controlled by specific innate immune signalling and by promoter polymorphisms and transcription factors that modulate the expression of genes controlling these pathways. Gene deletions that disturb innate immune activation either favour asymptomatic bacteriuria or create acute morbidity and disease. Promoter polymorphisms and transcription factor variants affecting those genes are associated with susceptibility in UTI-prone patients. Summary It is time to start using genetics in UTI-prone patients, to improve diagnosis and to assess the risk for chronic sequels such as renal malfunction, hypertension, spontaneous abortions, dialysis and transplantation. Furthermore, the majority of UTI patients do not need follow-up, but for lack of molecular markers, they are unnecessarily investigated.